ADVANTAGES OF SUPERVISED TEACHING ALGORITHMS (Modern education and development, 2025)
The article analyzes the advantages of supervised learning algorithms. The article highlights the advantages of supervised learning algorithms in providing accurate and reliable results, assisting in data-based decision-making, reducing errors, and wide application areas.